Environmental Governance in Indonesia - Triyanti, Annisa; Indrawan, Mochamad; Nurhidayah, Laely; Marfai, Muh Aris (Environment & Policy, 2023)
This open access book presents the state-of-the-art environmental governance research and practices in Indonesia. It offers a wide scope, covering different sectors (e.g., forestry, mining) and geographical landscapes (e.g., inland and coastal areas). This book engages with existing theories and frameworks, including Earth System Governance, Adaptive and Interactive Governance, among others to trigger a debate regarding the operationalization of such concepts, which are mostly developed for the Global North context. It is also our ambition to incorporate more empirical knowledge from local contexts to indicate research gaps and future directions for environmental governance research agenda to be more diverse, inclusive, and facilitate the incorporation of inter-and transdisciplinary knowledge. This book will be useful for researchers, students, practitioners, and policymakers who are interested in the field of environmental governance, especially in Indonesia. Indonesia is one of the countries with the fastest-growing economies in Asia. Indonesia is rich in natural resources but also suffers from overexploitation and environmental threats exacerbated by climate and human pressures. Along with the growing global ambitions for achieving sustainable development and capacity to adapt to current and future threats, including climate change impacts and disaster risk, Indonesia's commitments to balance development while safeguarding a good environmental status are also increasing. The challenge is on how to govern complex and systemic natural, social and governance systems while adhering to the principle of equity and justice? As it will require more than traditional hierarchical modes of governance and current regulatory instruments (i.e., law and regulations). This is an open access book.